Mechanical properties of semi-lightweight concrete containing nano-palm oil clinker powder - H. M., Hamada; A. A., Alattar; F. M., Yahaya; K., Muthusamy; Tayeh, Bassam A. (Elsevier Ltd., 2021)
The traditional materials used in concrete will run out some day. Therefore, waste materials can be used as an alternative material in concrete production. Palm oil clinker (POC) is one of these wastes. A new method to improve the performance of waste material characteristics is to treat and grind the waste materials to achieve nano-particle size. This study focused on the improvement of concrete strength by using different proportions of nano-palm oil clinker powder (NPOCP) as cement replacement, with a full replacement of POC as the coarse aggregate. Numerous replacement levels for cement have been conducted using NPOCP with 0% as the control mix and 10%, 20%, 30% and 40% of the total binder weight to test slump, density and compressive strength. Results illustrated that the workability of semi-lightweight aggregate concrete (semi-LWAC) increases along with the increase of NPOCP content. Density also decreases along with the increase of NPOCP in the concrete mix. Moreover, the NPOCP with 40% as replacement level has the lowest compressive strength value among all other mixtures, and the 10% replacement level has the highest compressive strength of 39 MPa.